Angular (full app) with Angular Material, Angularfire and NgRx (Packt Publishing, 2018)
"This course will take you on a journey where you'll you will learn to build a real Angular app using Angular, Angular Material, AngularFire (+ Firebase with Firestore), and NgRx. Angular is an amazing frontend framework with which you can build powerful web applications; we will add real-time database functionalities and see our updates almost before we make them here. This course offers a brief refresher on Angular, a detailed introduction into Angular Material, and a realistic app that uses many Angular Material components."--Resource description page